Empathy and Respect: Building Counselor-Counselee Relationships Through Students' Eyes - Alya Adinda Dewi Chotifa; Muwakhidah Muwakhidah; Azzahra Febriana Kurnia Santoso; Maria Sri Vandriyani; Ofilia Wahyu Ridho Pratama; Siti Auliya Putri Allifah; Alya Adinda Dewi Chotifa; Muwakhidah Muwakhidah; Azzahra Febriana Kurnia Santoso; Maria Sri Vandriyani; Ofilia Wahyu Ridho Pratama (Universitas Negeri Malang, 2025)
Empathy and respect are important skills that counselors must have. However, there is not much research that reveals the level of both in a counselor. The aim of this research is to determine the profile of empathy and respect used by counselors in building relationships between counselors and counselees. The method used is quantitative through descriptive design and a survey approach with a subject of 99 students and using an empathy and respect questionnaire according to Carkhuff's theoretical construct. This research uses data analysis techniques, namely descriptive statistics. The research results show the counselor's level of empathy based on the students' perspective with the percentage results in the very high category with a score of 52%. Meanwhile, respect is in the very high category with a score of 48%. Thus, it can be concluded that the level of empathy and respect for counselors is in the very high category.